2021
DOI: 10.21203/rs.3.rs-131488/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cycloalkane-modified amphiphilic polymers provide direct extraction of membrane proteins for CryoEM analysis

Abstract: Membrane proteins are essential for cellular growth and homeostasis, making up a large proportion of therapeutic targets. However, the necessity for a solubilising agent to extract them from the membrane creates significant challenges in their structural and functional study. Although amphipols have been very effective for single-particle electron cryo-microscopy (cryoEM) and mass spectrometry, they rely on initial detergent extraction before exchange into the amphipol environment. Therefore, circumventing thi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…A recent study has reported that phospholipids were present in samples of Acrb-solubilized and purified in CyclAPols . However, the lipid analysis, performed by thin layer chromatography, did not permit to accurately identify and quantify lipid species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has reported that phospholipids were present in samples of Acrb-solubilized and purified in CyclAPols . However, the lipid analysis, performed by thin layer chromatography, did not permit to accurately identify and quantify lipid species.…”
Section: Resultsmentioning
confidence: 99%
“…Knowing that extraction efficiencies can vary between prokaryotic and eukaryotic MPs, additional work would be needed to confirm this property. The CyclAPols (now supplied by Cube Biotech) have recently been validated as appropriate amphipathic environments for determining high-resolution structures of MPs by cryo-EM, which bodes well for their usefulness. One may add that APol A8-35 can be chemically modified with different types of functionalities, such as affinity tags or fluorophores, without affecting its MP-stabilizing properties.…”
Section: Discussionmentioning
confidence: 99%
“…Mimicking this property of SMA eliminates the requirement for classical detergent mediated extraction and subsequent APol exchange that can, in some cases, result in MP destabilisation. A recent preprint reported the use of CyclAPols in the solubiliation of the model bacterial membrane transporter AcrB which subsequently yielded a 3.2 Å Cryo-EM structure [ 92 ].…”
Section: Amphipolsmentioning
confidence: 99%
“…It is worth to be pointed out that Marconnet et al have recently revealed a novel cryo-EM compatible polymers, cycloalkane-modified amphipols (CyclAPols), which can provide a native membrane protein extraction but could not retain the well-organized native lipids plug within transmembrane (TM) domains. 22,23 (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth to be pointed out that Marconnet et al have recently revealed a novel cryo-EM compatible polymers, cycloalkane-modified amphipols (CyclAPols), which can provide a native membrane protein extraction but could not retain the well-organized native lipids plug within transmembrane (TM) domains. 22,23 Among the membrane-active polymers, the commercial SMA2000 with defined ratio 2: 1 of hydrophobic: hydrophilic domains has exhibited as the most effective solubilizer for several membrane protein model systems. 7,9,12,24 To overcome the limitations of SMA2000 and retain a good extraction efficiency, our novel polymers were produced through individual grafting of or 100%, herein, "x" values were varied to explore how such contents and structures of the amines influence membrane solubilization, purification, and stability.…”
Section: Introductionmentioning
confidence: 99%